Utilization of Biopori as a Composting Media and Management of Rainwater Flooding in the As Sakinah Mosque Area, Mulyorejo Village, Sukun District, Malang City - Artiyani, Anis; Ashari, Mochammad Ibrahim; Sudiasa, I Nyoman; Roostrianawaty, Nenny; Rhofita, Erry Ika; Wadu, Evelyn Darmawulan Djami; Yoseph, Cindy Sandrina; Wijaya, Ida Bagus Prama; Gabriel, Marchello; Sa’diyah, Maia Hana (Indonesian Journal of Advanced Social Works, 2023)
Biopori is a simple technology that can do a lot. This can be used as water absorption, reducing waterlogging, as a composting container, and of course fertilizing the soil. This program is run through a learning by doing system that uses material modules as teaching media. Based on the existing conditions, the counseling technique was carried out by gathering several local residents and providing direct practical explanations on how to install biopores and explaining the advantages of biopores as a means of storing water absorption as well as a composting medium for organic waste. The aim of this service is to master the technique of making biopores and prove the benefits of biopores in being able to overcome puddles while storing water reserves in the soil and can also be used as a composter for organic waste which can later be used as compost. So that the inconvenience of passing residents, especially those going to the mosque for worship, because there is standing water in the paving area of the mosque and reducing the volume of residents' waste, especially organic waste, can be resolved.